Aluminum oxide copper-chromium alloy material, preparation method and electrical contact
By optimizing the ratio of copper, chromium and alumina in the copper-chromium aluminum oxide alloy material and using permeability and annealing treatment, the problem of poor performance of existing copper-chromium electrical contacts at high voltages is solved, and the electrical contact materials with high wear resistance and arc ablation resistance are achieved, which improves the reliability and life of the circuit breaker.
Patent Information
- Application Number
- CN202411655452.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-14
AI Technical Summary
Existing copper-chromium electrical contacts are difficult to meet the performance requirements of arc ablation and mechanical wear resistance at high voltage levels, and alumina particles are prone to agglomeration during the preparation process, affecting material performance.
Alumina copper-chromium alloy material is used to optimize the ratio of copper, chromium and aluminum oxide to prepare alumina diffused copper alloy body and chromium blank, and permeability treatment is performed under high temperature vacuum conditions, followed by annealing to improve the material's wear resistance and arc ablation resistance.
It significantly improves the breaking performance of electrical contacts, extends the service life of high-voltage vacuum circuit breakers, reduces equipment and operation and maintenance costs, and achieves high reliability and long-life electrical contact materials.
Smart Images

Figure CN119614976A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrical materials, and in particular relates to an aluminum oxide copper-chromium alloy material, a preparation method and an electric contact. Background Art
[0002] Circuit breakers are a type of switchgear widely used in power systems, with excellent insulation performance and fast and reliable breaking capabilities. Electrical contacts are the core of circuit breakers. The quality of electrical contact materials is directly related to the performance of circuit breakers, which in turn affects the safety and stability of power grids. The quality of electrical contact materials directly affects the breaking capacity, dielectric recovery strength and electromechanical life of circuit breakers, which in turn affects the transformation of ultra-high voltage power transmission and smart grids.
[0003] Existing electrical contacts are mainly made of copper-chromium alloy materials, which are difficult to better meet the performance requirements of arc erosion and mechanical wear resistance under high voltage level interruption. The traditional method of preparing electrical contacts generally includes ball milling, vacuum hot pressing sintering and other steps to disperse aluminum oxide particles as a reinforcement phase into the copper-chromium alloy. During the preparation process, aluminum oxide particles are prone to agglomeration, and the prepared electrical contacts are often difficult to truly improve in terms of wear resistance and arc erosion resistance, which greatly limits the application of electrical contacts.
[0004] Therefore, there is still a need to improve the copper-chromium electrical contact components and preparation methods to obtain high-performance copper-chromium electrical contact materials. Summary of the invention
[0005] The purpose of the invention is to solve the problem that the existing copper-chromium electric contact has poor wear resistance and arc erosion resistance.
[0006] The purpose of the present invention is to adopt the following technical solutions to achieve:
[0007] The invention provides an aluminum oxide copper chromium alloy material. The components of the aluminum oxide copper chromium alloy material include, by weight percentage, 0.02% to 2.5% aluminum oxide, 47.5% to 49.98% copper, and the balance being chromium and its inevitable impurities.
[0008] Based on the same inventive concept, the present invention also provides a method for preparing the aluminum oxide copper chromium alloy material, comprising: blank preparation: preparing an aluminum oxide dispersed copper alloy body and a chromium blank respectively; solution infiltration treatment: stacking the aluminum oxide dispersed copper alloy body and the chromium blank in a mold and performing solution infiltration under high temperature and vacuum conditions to obtain a solution infiltration alloy body; annealing treatment: annealing the solution infiltration alloy body to obtain the aluminum oxide copper chromium alloy material.
[0009] Preferably, in the blank preparation step, the preparation method of the alumina dispersed copper alloy body includes: weighing Cu-Al alloy powder and Cu2O powder and mixing them evenly; placing the evenly mixed powder into a closed container and preparing a nano Al2O3-Cu composite powder by high-temperature internal oxidation; and obtaining the alumina dispersed copper alloy body by pressing the nano Al2O3-Cu composite powder.
[0010] Preferably, the mass percentage content of Al in the Cu-Al alloy powder is W1, and the value range of W1 is 0.01% to 4.33%.
[0011] Preferably, the masses of the Cu-Al alloy powder and the Cu2O powder are M1 and M2 respectively, and M1 and M2 have the following relationship: M2=M1×8W1.
[0012] Preferably, the Cu-Al alloy powder is prepared by water atomization or nitrogen atomization.
[0013] Preferably, the particle size of the Cu-Al alloy powder is 0.5 μm to 4 μm.
[0014] Preferably, the particle size of the Cu2O powder is 0.6 μm to 5 μm.
[0015] Preferably, the redox temperature of the high-temperature internal oxidation is 500° C. to 800° C., and the reduction time is 20 min to 60 min.
[0016] Preferably, in the blank preparation step, the preparation method of the chromium blank comprises: weighing chromium powder equal to the sum of the mass of the Cu-Al alloy powder and the Cu2O powder; and obtaining the chromium blank by pressing the chromium powder.
[0017] Preferably, the particle size of the chromium powder is 20 μm to 75 μm.
[0018] Preferably, in the green body preparation step, an isostatic pressing machine is used to prepare the green body, the isostatic pressing machine is set to have a pressure of 200 MPa to 600 MPa, and a pressure holding time of 20 min to 50 min.
[0019] Preferably, a solution infiltration furnace is used in the solution infiltration treatment step, and the vacuum degree of the solution infiltration furnace is not greater than 1×10 - 2 Pa, the dissolution temperature is 1100°C to 1500°C, and the dissolution time of the dissolution treatment is 1h to 4h.
[0020] Preferably, in the annealing step, the annealing temperature of the annealing treatment is 400° C. to 700° C., and the annealing time of the annealing treatment is 1 h to 4 h.
[0021] Based on the same inventive concept, the present invention also provides an electric contact applied to a high-voltage vacuum circuit breaker, wherein the electric contact is made of the aluminum oxide copper-chromium alloy material.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention provides an aluminum oxide copper chromium alloy material. The components of the aluminum oxide copper chromium alloy material include, by weight percentage: 0.02% to 2.5% aluminum oxide, 47.5% to 49.98% copper, and the balance is chromium and its inevitable impurities. The material has excellent wear resistance, arc erosion resistance and mechanical properties by optimizing and controlling the proportion of copper, chromium and aluminum oxide in the material. The material is used to make electrical contact parts of high-voltage vacuum circuit breakers, improves the breaking performance of the electrical contacts, realizes high reliability and long life of high-voltage vacuum circuit breakers, and saves equipment costs and operation and maintenance costs.
[0024] In addition, the present invention also provides a method for preparing an aluminum oxide copper-chromium alloy material, which includes blank preparation, infiltration treatment and annealing treatment. In which, an aluminum oxide dispersed copper alloy body and a chromium blank are prepared separately, the aluminum oxide dispersed copper alloy body and the chromium blank are stacked in a mold and infiltrated under high temperature and vacuum conditions to obtain an infiltrated alloy body, and the infiltrated alloy body is annealed to obtain an aluminum oxide copper-chromium alloy material. Through such steps, an aluminum oxide dispersed copper alloy body is first prepared, and then the dispersed aluminum oxide and copper are uniformly infiltrated and dispersed into the chromium blank through infiltration treatment to form an aluminum oxide dispersed copper alloy body, thereby improving the uniformity of the dispersion distribution of aluminum oxide in the material and avoiding the problem of easy agglomeration of aluminum oxide directly added to the copper-chromium alloy in the traditional process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a flow chart of the main steps in preparing the aluminum oxide copper chromium alloy material of the present invention;
[0026] Figure 2 Detailed step flow chart of the preparation of the aluminum oxide copper chromium alloy material of the present invention. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred solution of the present invention is described below in conjunction with the best embodiment of a specific application. Obviously, the described embodiment is only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0028] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0029] The invention provides an aluminum oxide copper chromium alloy material. The components of the aluminum oxide copper chromium alloy material include, by weight percentage, 0.02% to 5% aluminum oxide, 45% to 49.98% copper, and the balance being chromium and its inevitable impurities.
[0030] Among them, by optimizing and controlling the proportion of components among copper, chromium and aluminum oxide, the prepared aluminum oxide copper-chromium alloy material has excellent wear resistance, arc erosion resistance and mechanical properties, and can be used to make electrical contact components of high-voltage vacuum circuit breakers.
[0031] like Figure 1 and Figure 2 As shown, the preparation method of the aluminum oxide copper chromium alloy material of the present invention comprises:
[0032] S1. Billet preparation: preparing an alumina dispersed copper alloy body and a chromium billet respectively;
[0033] S2, solution infiltration treatment: stacking the alumina dispersed copper alloy body and the chromium blank body in a mold and performing solution infiltration under high temperature vacuum conditions to obtain a solution infiltration alloy body;
[0034] S3. Annealing treatment: annealing the infiltrated alloy body to obtain an aluminum oxide copper chromium alloy material.
[0035] Specifically, Figure 2 As shown, in the S1 blank preparation step, the specific steps of preparing the alumina dispersed copper alloy body include:
[0036] S1a1, weighed Cu-Al alloy powder and Cu2O powder and mix them evenly;
[0037] S1a2, placing the uniformly mixed powder into a sealed container and preparing Al2O3-Cu composite powder with a size of hundreds of nanometers by high-temperature internal oxidation;
[0038] S1a3, the nano-Al2O3-Cu composite powder is pressed to obtain an alumina dispersed copper alloy body.
[0039] In step S1a1, the particle size of the Cu2O powder is 0.6 μm to 5 μm. In step S1a1, the Cu-Al alloy powder with a particle size of 0.5 μm to 4 μm is prepared by water atomization or nitrogen atomization.
[0040] The mass percentage content of Al in the Cu-Al alloy powder is W1, and the masses of the Cu-Al alloy powder and the Cu2O powder are M1 and M2 respectively.
[0041] Among them, the value range of W1 is 0.01% to 4.33%, and M1 and M2 have the following relationship: M2=M1×8W1.
[0042] The masses of the Cu-Al alloy powder and the Cu2O powder are calculated and weighed respectively according to the above relationship formula, and the two weighed powders are stirred evenly.
[0043] In step S1a2, the uniformly stirred powder is placed in a sealed container, and in a hydrogen atmosphere, Cu2O and Cu-Al undergo a high-temperature internal redox reaction to generate nano Al2O3-Cu composite powder. The redox temperature is 500°C to 800°C, and the redox time is 20min to 60min. Excessive hydrogen is introduced during the redox process to ensure that the oxygen in Cu2O is completely exhausted.
[0044] In step S1a3, the prepared nano-Al2O3-Cu composite powder is pressed to prepare a columnar alumina dispersed copper alloy body.
[0045] In addition, if Figure 2 As shown, in the S1 blank preparation step, the specific steps of preparing the chromium blank include:
[0046] S1b1, weigh chromium powder equal to the sum of the mass of Cu-Al alloy powder and Cu2O powder;
[0047] S1b2, chromium powder is pressed to obtain a columnar chromium blank. The diameter of the chromium blank is the same as that of the alumina dispersed copper alloy body. The particle size of the chromium powder is 20 μm to 75 μm, and the chromium blank has a porous skeleton structure after pressing.
[0048] It should be noted that before the chromium powder is formed through a pressing process, an appropriate amount of a forming agent (such as paraffin) can be added to the chromium powder to better assist in the forming of the chromium blank and retain a certain porous skeleton structure.
[0049] In addition, in the above steps S1a3 and S1b2, the alumina dispersed copper alloy body and the chromium blank are respectively prepared by an isostatic pressing machine, the isostatic pressing machine is set at a pressure of 200 MPa to 600 MPa, and the pressure holding time is 20 min to 50 min.
[0050] like Figure 2 As shown, after the above-mentioned alumina dispersed copper alloy body and chromium blank are completed, the infiltration treatment is performed. In the S2 infiltration treatment step, the stacked alumina dispersed copper alloy body and chromium blank are placed in an infiltration furnace together with the mold for treatment. The vacuum degree in the infiltration furnace is not greater than 1×10 -2Pa, the dissolution temperature is 1100℃~1500℃, and the dissolution time is 1h~4h.
[0051] In the S3 annealing step, an annealing furnace is used for annealing, the annealing temperature is 400° C. to 700° C., and the annealing time is 1 hour to 4 hours.
[0052] Through the preparation method, Cu2O and Cu-Al alloy powder are uniformly mixed and then pre-prepared by a high-temperature oxidation-reduction method to prepare a copper alloy body containing uniformly dispersed nano-alumina. When the alumina-dispersed copper alloy body and the chromium blank are subjected to vacuum infiltration treatment, alumina and copper simultaneously diffuse and infiltrate into the chromium blank and its porous skeleton structure to form an alumina-dispersed copper alloy body, thereby improving the uniformity of the dispersion distribution of alumina in the overall material, thereby improving the overall performance of the alloy, and avoiding the problem of agglomeration caused by directly adding alumina to the copper-chromium alloy in the traditional process.
[0053] The aluminum oxide copper-chromium alloy materials provided in the following examples are all made using the above-mentioned types of raw materials and preparation methods, with the only difference being that the raw material parameters and preparation parameters used in the examples are different.
[0054] Examples 1-6
[0055] Specifically, Table 1 is a comparison table of the percentage content of the components of the aluminum-copper-chromium alloy material after preparation in Examples 1-6:
[0056] Table 1
[0057] Alloy material composition Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 <![CDATA[Al2O3(%)]]> 0.02 0.1 0.5 1 2.5 5 Cu(%) 49.98 49.9 49.5 49 47.5 45 Cr and unavoidable impurities (%) 50 50 50 50 50 50
[0058] Among them, the mass percentage of Al2O3 in the aluminum oxide copper-chromium alloy material is defined as W2. According to the formula W2=9W1 / (17-72W1), the mass percentage content W1 of Al in the Cu-Al alloy powder to be selected can be calculated, and then the specific masses of the Cu-Al alloy powder and Cu2O powder in the preparation raw material can be converted respectively according to the formula M2=M1×8W1, thereby ensuring that the mass percentage content of Al2O3 in the prepared aluminum oxide copper-chromium alloy material is within the designed range.
[0059] In the present embodiment 1-6, the total mass of the Cu-Al alloy powder and the Cu2O powder is based on 500g as the reference ingredient (M1+M2=500).
[0060] Specifically, Table 2 is a comparison table of raw material parameters for preparing the aluminum oxide copper chromium alloy materials in Examples 1-6:
[0061] Table 2
[0062] Raw material parameters Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 w1 of Cu-Al (%) 0.01 0.05 0.27 0.55 1.48 4.33 Cu-Al alloy powder M1 (g) 499.15 495.7 478 457 394 365 <![CDATA[Cu2O powder M2(g)]]> 0.85 4.3 22 43 106 135 Cr powder(g) 500 500 500 500 500 500 Cu-Al alloy powder particle size (μm) 4 3 1.5 0.5 0.5 0.5 <![CDATA[Particle size of Cu2O powder (μm)]]> 5 3 1.5 0.6 0.6 0.6 Cr powder particle size (μm) 20 35 40 60 75 75
[0063] Table 3 is a comparison table of preparation parameters of the aluminum oxide copper chromium alloy materials in the preparation examples 1-6:
[0064] Table 3
[0065]
[0066] Comparative Example
[0067] This comparative example provides a copper-chromium alloy material, which comprises, by weight percentage, 50% copper and the remainder chromium and its inevitable impurities.
[0068] The preparation method of the copper-chromium alloy material of the comparative example comprises:
[0069] 500 g of Cu powder and 500 g of chromium powder were weighed in a mass ratio of 1:1, wherein the Cu powder had a particle size of 0.5 μm and the chromium powder had a particle size of 20 μm.
[0070] The Cu powder and the chromium powder were respectively passed through a press to prepare a columnar copper billet and a chromium billet. The applied pressure of the press was 500 MPa and the pressure holding time was 40 minutes.
[0071] The copper blank and the chromium blank are stacked in a mold and infiltrated under high temperature and vacuum conditions to obtain an infiltration alloy body. The vacuum degree in the infiltration furnace under the infiltration state is not greater than 1×10 -2 Pa, the dissolution temperature is 1400℃ and the dissolution time is 3h.
[0072] Annealing treatment: annealing the infiltrated alloy body in an annealing furnace to obtain an aluminum oxide copper chromium alloy material, wherein the annealing temperature is 450° C. and the annealing time is 3 hours.
[0073] Test Results
[0074] The alloy samples prepared in the above Examples 1-6 and Comparative Examples were subjected to performance tests. Among them, the ablation resistance was tested by mass loss after 50 arc ablation tests under 10KV conditions, the conductivity was tested by eddy current conductivity meter, and other test items were tested according to conventional methods. Table 4 is a comparison table of the test performance results of the alloy samples in Examples 1-6 and Comparative Examples.
[0075] Table 4
[0076]
[0077] By comparison, it can be seen that the overall performance indexes of the aluminum oxide copper chromium alloy materials in Examples 1-6 of the present invention are significantly better than those in the comparative examples. Among them, Examples 4-5 are more excellent in wear resistance and ablation resistance.
[0078] It should be noted that, although the above embodiment only lists some components of the aluminum oxide copper chromium alloy material to demonstrate the performance of the material; however, according to practical applications, those skilled in the art can further design the aluminum oxide content in the aluminum oxide copper chromium alloy material, and its mass percentage range includes: any one or more of 0.02% to 0.05%, 0.06% to 0.12%, 0.13% to 0.6%, 0.7% to 1%, and 1% to 5%. Among them, the total mass percentage of aluminum oxide and copper in the aluminum oxide copper chromium alloy material is 50%.
[0079] Example 7
[0080] Based on the same inventive concept, this embodiment also provides an electric contact, which is applied to a high-voltage vacuum circuit breaker, and the electric contact is made of the aluminum oxide copper chromium alloy material prepared in any one of Examples 1 to 6. According to the mechanical structure drawing of the electric contact, the above-mentioned aluminum oxide copper chromium alloy material is machined to obtain a high-ablation-resistant aluminum oxide copper chromium electric contact applied to a high-voltage vacuum circuit breaker.
[0081] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of the claims of the present invention to be approved.
Claims
1. An aluminum oxide copper-chromium alloy material, characterized in that: Calculated by weight percentage, the components of the aluminum oxide copper chromium alloy material include: 0.02% to 5% aluminum oxide, 45% to 49.98% copper, and the balance being chromium and its inevitable impurities.
2. A method for preparing the aluminum oxide copper chromium alloy material according to claim 1, characterized in that: include: Preparation of green body: preparing alumina dispersed copper alloy body and chromium green body respectively; Infiltration treatment: stacking the alumina dispersed copper alloy body and the chromium blank body in a mold and infiltrating them under high temperature and vacuum conditions to obtain an infiltration alloy body; Annealing treatment: annealing the infiltration alloy body to obtain the aluminum oxide copper chromium alloy material.
3. The method for preparing the aluminum oxide copper chromium alloy material according to claim 2, characterized in that: In the blank preparation step, the method for preparing the alumina dispersed copper alloy body comprises: Weigh Cu-Al alloy powder and Cu2O powder and mix them evenly; The uniformly mixed powder is placed in a sealed container and subjected to high temperature internal oxidation to prepare nano-Al2O3-Cu composite powder; The nano Al2O3-Cu composite powder is pressed to obtain the alumina dispersed copper alloy body.
4. The method for preparing the aluminum oxide copper chromium alloy material according to claim 3, characterized in that: The mass percentage content of Al in the Cu-Al alloy powder is W1, and the value range of W1 is 0.01% to 4.33%.
5. The method for preparing the aluminum oxide copper chromium alloy material according to claim 4, characterized in that: The masses of the Cu-Al alloy powder and the Cu2O powder are M1 and M2 respectively, and M1 and M2 have the following relationship: M2=M1×8W1.
6. The method for preparing the aluminum oxide copper chromium alloy material according to claim 3, characterized in that: The Cu-Al alloy powder is prepared by water atomization or nitrogen atomization.
7. The method for preparing the aluminum oxide copper chromium alloy material according to claim 3, characterized in that: The particle size of the Cu-Al alloy powder is 0.5 μm to 4 μm.
8. The method for preparing the aluminum oxide copper chromium alloy material according to claim 3, characterized in that: The particle size of the Cu2O powder is 0.6 μm to 5 μm.
9. The method for preparing the aluminum oxide copper chromium alloy material according to claim 3, characterized in that: The redox temperature of the high-temperature internal oxidation is 500° C. to 800° C., and the reduction time is 20 min to 60 min.
10. The method for preparing the aluminum oxide copper chromium alloy material according to claim 3, characterized in that: In the blank preparation step, the preparation method of the chromium blank comprises: Weighing chromium powder equal to the sum of the mass of the Cu-Al alloy powder and the Cu2O powder; The chromium powder is pressed into the chromium blank.
11. The method for preparing the aluminum oxide copper chromium alloy material according to claim 10, characterized in that: The particle size of the chromium powder is 20 μm to 75 μm.
12. The method for preparing the aluminum oxide copper chromium alloy material according to claim 2, characterized in that: In the green body preparation step, an isostatic pressing machine is used to prepare the green body, the isostatic pressing machine is set at a pressure of 200Mpa to 600Mpa, and the pressure holding time is 20min to 50min.
13. The method for preparing the aluminum oxide copper chromium alloy material according to claim 2, characterized in that: In the infiltration treatment step, an infiltration furnace is used, and the vacuum degree of the infiltration furnace is not greater than 1×10 -2 Pa, the dissolution temperature is 1100°C to 1500°C, and the dissolution time of the dissolution treatment is 1h to 4h.
14. The method for preparing the aluminum oxide copper chromium alloy material according to claim 2, characterized in that: In the annealing step, the annealing temperature of the annealing is 400° C. to 700° C., and the annealing time of the annealing is 1 hour to 4 hours.
15. An electrical contact, characterized in that: Applied to a high-voltage vacuum circuit breaker, the electrical contact is made of the aluminum oxide copper-chromium alloy material as claimed in claim 1.